UniSClub - mobile application for students club in MARA University of Technology (UiTM) / Mohamad Nazrul Asraf Sabaruddin - Sabaruddin, Mohamad Nazrul Asraf (2019)
Nowadays, nearly everyone has a smartphone and the number of smartphone users are already in the billions. We use our smartphone for everything such as ordering food and getting a ride to go somewhere. This leads to smartphone becoming a huge part in our daily life. However, for the club members the communication between them are done only using a group chat application. The development of the mobile application for the students’ club in UiTM is focusing to provide a medium for club members to communicate with each other. The mobile application allows user to post announcement or information which allows another user to view and interact with it. The user also able to edit their own profile by adding their full name, class and change their username. The user is also able to edit their account setting such as changing their email and password. User are able to join club created by another user. The backend for this mobile application is using Firebase. For the user authentication such as login and registration, Firebase Authentication is used. Firebase Realtime Database is used to store user’s data, posts, and club’s data. For the user profile image, Firebase Storage is used. This mobile application development is developed using Android Studio.